2017
DOI: 10.7771/2159-6670.1160
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Disadvantages of Using Internet-Based Survey Methods in Aviation-Related Research

Abstract: Within the last decade, numerous online populations, such as SurveyMonkeyH and Amazon's Mechanical TurkH (MTurk), have been established allowing researchers to gather data involving diverse populations. These resources offer an alternative to traditional laboratory settings hosted at universities, where many studies utilize students as the available and accessible population. While these online portals do provide new opportunities, they also contain unique advantages and disadvantages. This paper synthesizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 19 publications
0
64
0
1
Order By: Relevance
“…First, our study used a cross-sectional design, and therefore we cannot discuss temporal aspects. Second, we used data of web-based survey, which includes potential disadvantages compared with face-to-face interviews and surveys using a paper questionnaire; we cannot negate the possibility that our participants might not be a representative sample [27]. For example, only individuals who could sign up for the website would be able to participate in online surveys.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study used a cross-sectional design, and therefore we cannot discuss temporal aspects. Second, we used data of web-based survey, which includes potential disadvantages compared with face-to-face interviews and surveys using a paper questionnaire; we cannot negate the possibility that our participants might not be a representative sample [27]. For example, only individuals who could sign up for the website would be able to participate in online surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of this study can only be generalized to the population of online users of MTurk. Although prior research has suggested that data gathered using MTurk are equally reliable as data collected from a laboratory setting (Buhrmester et al, 2011;Germine et al, 2012;Rice et al, 2017). Another limitation of this study is the examination of perceptions of consumers from only two counties, and the recognition that consumers may have limited perceptions on weather conditions.…”
Section: Limitationsmentioning
confidence: 91%
“…MTurk provides participants who are willing to complete human intelligence tasks in exchange for payment. MTurk data have been shown to be as reliable as standard laboratory data (Buhrmester, Kwang, & Gosling, 2011;Germine et al, 2012;Rice, Winter, Doherty, & Milner, 2017).…”
Section: Participantsmentioning
confidence: 92%
“…The primary data collection methods were informed by the fact that 26% of Kenya's estimated population of 52.2 million have access to the Internet, while 80.4% of the adult population have mobile subscriptions with Internet access capabilities [1,73]. In this context, an online survey was chosen mainly for four reasons: (1) the interest of stakeholders (in this case CBT associations and networks) and their willingness to provide feedback; (2) time and cost constraint; (3) to access a large and geographically diverse population; and (4) to get quick responses as supported by the views of earlier researchers [74][75][76][77]. Contemporary scholars continue to argue that the scale and real-time nature of online and social media possibilities can be used to expand our range of insights into new questions and domains [77][78][79][80].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, an online survey was chosen mainly for four reasons: (1) the interest of stakeholders (in this case CBT associations and networks) and their willingness to provide feedback; (2) time and cost constraint; (3) to access a large and geographically diverse population; and (4) to get quick responses as supported by the views of earlier researchers [74][75][76][77]. Contemporary scholars continue to argue that the scale and real-time nature of online and social media possibilities can be used to expand our range of insights into new questions and domains [77][78][79][80]. This research thus used an online survey to get feedback from interested and engaged tourism stakeholders from a diverse geographical and perceptual reach given time and cost constraints.…”
Section: Methodsmentioning
confidence: 99%